Growth and Phytomass Production in Leucaena leucocephala Under High Density Plantations on Degraded Lands of Doon Valley - Gupta, R. K.; Agarwal, M. C.; Kumar, Nirmal (Indian Forester, 1996)
Studies on plantation of Leucaena leucocephala were conducted to establish linear prediction ,model of leaf/wood under three different spacings i.e O.5m × O.5m, 0.5 × 1.0m and O.5m × t.5m on degraded riverbed soils of Dehradun. The studies showed that the prediction model of leaf/wood yield with all the three variables was the most reliable model in all the three spacings. The next best reliable linear prediction model ofleaf/wood yield was with two variables, One as height and another either basal diameter or DBH as predictors in all the three spacings.